IMPLEMENTATION OF PRESIDENTIAL REGULATION NO. 72/2021 ON STUNTING REDUCTION: A STRUCTURED COMPARATIVE NARRATIVE REVIEW WITH SYSTEMATIC SEARCH PROCEDURES OF FOUR INDONESIAN REGIONS - Hanafi, Imam; Trisulandari, Kartika (Journal of Community Health and Preventive Medicine, 2026)
Stunting remains a significant public health challenge in Indonesia, reflecting chronic undernutrition and unequal access to health and nutrition services. This study examined the implementation of Presidential Regulation No. 72 of 2021 through a structured comparative narrative review with systematic searches of peer-reviewed literature from 2019 to 2023, focusing on Bandung Regency, Jember Regency, Batam City, and Padang City. Data synthesis compared intervention models, implementation strategies, measurable outcomes, and contextual influences. Results varied by region. Jember achieved a marked decline in stunting, from about 37.94% in 2020 to 11.74% by the end of 2021, supported by a formally mandated multi‑sectoral coordination body (TPPS). Batam reported falling prevalence from 7.2% (2020) to 2.4% (2022) after adopting an integrated convergence policy across seven agencies. Bandung implemented a 1,000 HPK inter‑agency framework but saw no measurable reduction during the study period, largely due to COVID‑19 disruptions. Padang showed incomplete cross-sectoral integration and an increasing trend (7.65% in 2018 to 9.6% in 2019). Where gains were documented, regions tended to share three features: a formal legal mandate, a dedicated budget line, and a structured coordination mechanism. That said, the non-experimental design of all four source studies means we cannot attribute observed prevalence changes to specific policy choices.